Development of Assessment Instrument Based on Higher Order Thinking Skills of Respiratory System of Grade XI of Senior High School - Ulfa, Maria; Kuswanti, Nur (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
Higher order thinking skills (HOTS) is a thinking process at a higher level. It is not just memorizing facts, it involves mental activity in an effort to explore complex, reflective, and creative experiences. Indicators for measuring higher order thinking skills are analyzing, evaluating, and creating. These three indicators include critical thinking, creative thinking, problem solving, and decision-making skills. This research aimed to describe validity, reliability, and level of difficulty test items of higher order thinking skills of Respiratory System matter. This was development research referring to the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The development of HOTS based assessment instrument was conducted at Biology Department – Universitas Negeri Surabaya and the trial activity was conducted at SMA Negeri 2 Sidoarjo. The theoretical validity was determined based on the results of the validation by matter expert and education expert using the validation sheet. The aspect of validity rated based on the aspects of concept, construction, language, and HOTS. The empirical validity was determined based on the result test items of HOTS on 40 students of class XI to identified empirical validity, reliability, and difficulty levels using the HOTS-based test items sheet. The results showed that the theoretical validity of the assessment instrument reached 98.19% and included in a very valid category. The empirical validity of 15 test items of HOTS were considered valid with the value of R (count) > 0.312. The reliability value of assessment instrument was 0.740 with a high level of consistency. The proportion of difficulty level was 60% with moderate category and 40% with difficult category. Based on the research results, it can be concluded that the HOTS-based assessment instrument of the Respiratory System was valid and reliable. Keywords: higher order thinking skills, theoretical validity, empirical validity, reliability, level of difficulty, Respiratory System.